nowledge of Human Resource Metrics and Engagement of Academic Staff of University of Lagos - Idowu Taofik (University Babes-Bolyai, 2019)
The predictors of employee engagement in an organization have been given much attention in the literature, but measuring value added of employee in terms of knowledge of human resource metrics as predictors of employee engagement requires more study especially within the Nigerian context. It is within this purview that this research work examined the perceived knowledge of human resource metrics in employee engagement with particular reference to the academic staff of University of Lagos. A quantitative research method was adopted using a convenient sampling technique to randomly select a total sample size of 103 respondents. Analyses of the data collected through the use of questionnaires were carried out using a regression statistical tool. The regression value for the null hypothesis was 0.388. Therefore, the findings revealed that the knowledge of human resource (productivity) metrics can be used to predict employee engagement. That is, knowledge about contributions, estimated rate of returns and wealth created by each employee will provide monetary arguments for workers/unions when suggesting investments in human resource which can be used to predict employee engagement in terms of their vigour, concentration and dedication to their work. Possible further studies should investigate the disclosure of human resource value in numeric terms so that employees could be better equipped to negotiate their terms and conditions of employment.